Ka whawhai tonu mātou = Struggle without end - Walker, Ranginui (Penguin, 2004)
A revised edition of the best-selling book containing two new chapters covering the last decade and a half. 'The struggle without end continues...' This is a revised edition of Dr Ranginui Walker's best-selling history of Aotearoa, New Zealand, from a Maori perspective. Since the mid-nineteenth century, Maori have been involved in an endless struggle for justice, equality and self-determination. In this book Dr Walker provides a uniquely Maori view, not only of the events of the past two centuries but beyond to the very origins of Maori people. In this updated edition Dr Walker has added new chapters covering the years of 1990, the flowering of the Maori culture and the growth of Maori political and economic power. Recent issues such as the foreshore and seabed legislation, the hikoi and Don Brash's Orewa speech are discussed.
Keywords: History; Kōrero nehe; Mana motuhake; Mautohe; Māori (New Zealand people); New Zealand; Politics and government; Rangatiratanga; Social conditions; Taipūwhenuatanga; Tikanga

Modern Māori: the Young Māori Party to Mana Motuhake - Sorrenson, M. P. K. (The Oxford illustrated history of New Zealand, 1990)
Keywords: History; New Zealand